2021
DOI: 10.3390/pharmaceutics13081159
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Perspective: New Potential Therapeutic for the Treatment of Neurological Diseases

Abstract: Several studies have shown that mesenchymal stromal/stem cells (MSCs) exert their neuroprotective and neurorestorative efficacy via the secretion of neurotrophic factors. Based on these studies, many clinical trials using MSCs for the treatment of neurological disorders have been conducted, and results regarding their feasibility and efficacy have been reported. The present review aims to highlight the characteristics and basic research regarding the role of MSCs in neurological disease and to discuss the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Therefore, their application has been tested in diverse pre-clinical animal models with encouraging results. In this section, we will concentrate on the findings of the beneficial actions of ASC, while the effect of MSC from other sources, e.g., of bone marrow or umbilical origin, are described elsewhere [ 11 , 35 , 60 ]. There are three ways to administrate ASC in vivo: (i) transplantation of cells, (ii) injection of ASC-CM, or (iii) injection of ASC-EV.…”
Section: Application Of Asc In Vivomentioning
confidence: 99%
“…Therefore, their application has been tested in diverse pre-clinical animal models with encouraging results. In this section, we will concentrate on the findings of the beneficial actions of ASC, while the effect of MSC from other sources, e.g., of bone marrow or umbilical origin, are described elsewhere [ 11 , 35 , 60 ]. There are three ways to administrate ASC in vivo: (i) transplantation of cells, (ii) injection of ASC-CM, or (iii) injection of ASC-EV.…”
Section: Application Of Asc In Vivomentioning
confidence: 99%
“…On the other hand, Clark et al have utilized the experimental autoimmune encephalomyelitis (EAE) murine model of MS to show that human placental MSC (hP-MSC)-derived EVs promote remyelination (Clark et al, 2019). They demonstrated that, as opposed to the control group, animals treated with hP-MSCs and hP-MSC-EVs displayed increased "differentiation of endogenous oligodendrocyte precursor cells into mature myelinating oligodendrocytes" (Mukai et al, 2021), resulting in an improved motor function in those groups. Furthermore, mice in these groups exhibited less DNA damage to oligodendrocytes.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Because MSCs can generate new neurons or other neural supporting cells, they are also an attractive target to develop treatment for neurodegenerative or neuroinflammatory disorders [ 29 , 30 ]. MSC-based therapy has been proven to be effective in ischemic stroke, neurodegenerative diseases, brain and spinal cord injuries [ 31 ], although in many cases, the exact mechanism of their therapeutic action remains to be elucidated.…”
Section: Mesenchymal Stem Cells (Mscs) and Their Therapeutic Potential For Brain Diseasesmentioning
confidence: 99%